DEVELOPMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS IN INCREASING COMPETITIVENESS IN THE MODERN ERA - Umar, Umar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The aims of the study were: (1) to describe the concept of developing MTs MiftahulMidadLumajang in increasing competitiveness; (2) to describe the development strategy of MTs MiftahulMidadLumajang district in increasing competitiveness; (3) to describe the implications of the development of MTs MiftahulMidadLumajang district in increasing competitiveness. This study uses a descriptive qualitative approach. The results showed that currently MTs MiftahulMidadLumajang district, the concept of school development in increasing competitiveness is in accordance with the concept of the vision, mission and goals of the school, learning is in accordance with the national curriculum and the local curriculum which has been established prioritizing outstanding students in both academic and non-academic fields. academics, flagship program Tartila method in understanding the Qur'an, improvement of facilities and infrastructure with the participation of stakeholders. Implementation of the curriculum administration management strategy to improve the quality of human resources (teachers and students), apply teacher and student discipline, establish good relations with the local community, and involve the community in school activities, then improve the quality of schools with 14 steps according to Crosby, and Implications in this research is in the form of customer satisfaction (community), conducive, pleasant, orderly environmental climate and quality that is in accordance with community expectations so that it can attract market (community) attention to send their children to MTs MiftahulMidad, Lumajang district